The impact of ethno-linguistic fractionalization on cultural measures: Dynamics, endogeneity and modernization - M Luiz, John (Journal of International Business Studies, 2015)
We introduce a measure called ethno-linguistic fractionalization (ELF), which captures the ethnic and/or linguistic diversity in a country and examine its implications on existing cultural measures. Not only do high levels of fractionalization affect the use of statistical means to account for cultural distance (CD), we show that it is not constant and therefore the dynamics of change need to be addressed. We pursue the study of the dynamics and potential endogeneity through an in-depth case study of South Africa over the course of the twentieth century. There is evidence of processes of modernization whereby economic progress impacts upon ELF. There are also complex interactions between the various measures of fractionalization and other sociopolitical and institutional variables. This provides us with an opportunity to bridge the CD and institutional distance literature as institutions impact upon culture and multinational enterprises, and institutional development is, in turn, affected by these. We call for a more realistic assessment of what is being captured in cultural measures and for recognition of the complexity of the notion of identity formation and its dynamics. Countries may have different underlying cultural schisms, including ELF, and its introduction will allow for a richer exploration of distance and diversity in International Business.